2021
DOI: 10.1002/ecs2.3671
|View full text |Cite
|
Sign up to set email alerts
|

A beneficial relationship: associated trees facilitate termite colonies (Macrotermes michaelseni) in Namibia

Abstract: In many tropical ecosystems, termites are important ecosystem engineers. Mound-building termite species often contribute to topographical landscape heterogeneity, and the associated accumulation of soil moisture and nutrients affects the spatial distribution of plant communities. Plants that grow next to the termite mound are known to benefit from the provided nutrients and water storage. The other way around, protection against erosion and cooling effects on the microclimate of the mounds imposed by associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 68 publications
(138 reference statements)
0
8
0
Order By: Relevance
“…This illustrates the long‐term advantages of tree‐associated colonies. Wildermuth et al (2021) suspect a self‐reinforcing cycle of both profiting ‘partners'. We conclude that the advantages of tree‐associated M. michaelseni mounds reflect within the intraspecific self‐thinning process, as Wildermuth et al (2021) showed that mound‐tree associations are regularly distributed.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This illustrates the long‐term advantages of tree‐associated colonies. Wildermuth et al (2021) suspect a self‐reinforcing cycle of both profiting ‘partners'. We conclude that the advantages of tree‐associated M. michaelseni mounds reflect within the intraspecific self‐thinning process, as Wildermuth et al (2021) showed that mound‐tree associations are regularly distributed.…”
Section: Discussionmentioning
confidence: 99%
“…If the hole was repaired the next day, we assumed the mound to be active. Mounds with open ventilation systems or no signs of activity were recorded as inactive and outwash pediment remains without any elevated mound structure were recorded as remnant (Grohmann et al 2010, Wildermuth et al 2021).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations